2020
DOI: 10.1002/jcp.30158
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 alleviates diabetic cardiomyopathy through regulation of endoplasmic reticulum stress and autophagy via insulin‐like growth factor‐binding protein 3

Abstract: Prolonged endoplasmic reticulum (ER) stress is the key driving force behind diabetic cardiomyopathy (DCM). Autophagy is extensively implicated in adaptive mechanisms for cell survival. Interleukin-33 (IL-33) is known to be a potent cardiac protector, but its roles in DCM, ER stress, and autophagy are currently unknown. We aimed to explore the effects of IL-33 on DCM and characterize the roles that ER stress and autophagy play in DCM. The effects of IL-33 on DCM, ER stress, and autophagy were characterized both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 57 publications
0
39
0
1
Order By: Relevance
“…P values were derived either from the t-test (a, d) or the ANOVA followed by SNK for multiple comparisons (b, c, e-h). 9 Oxidative Medicine and Cellular Longevity without concurrent systolic defects [19]. However, the abovementioned study showed a significant reduction of LVEF in db/db mice [4], which implied a late stage of DCM or other coexistent causes of cardiac insults.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…P values were derived either from the t-test (a, d) or the ANOVA followed by SNK for multiple comparisons (b, c, e-h). 9 Oxidative Medicine and Cellular Longevity without concurrent systolic defects [19]. However, the abovementioned study showed a significant reduction of LVEF in db/db mice [4], which implied a late stage of DCM or other coexistent causes of cardiac insults.…”
Section: Discussionmentioning
confidence: 93%
“…Male C57BLKsJ-db/db mice were used to establish the spontaneous T2DM and DCM as our previous report [19]. Age-matched male C57BLKsJ-m/m mice were used as the control [19]. Mice were kept in a 12 h light/dark cycle with free access to chow and water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have found that the confounding effects of the classical risk factors that coexist in diabetes, such as hyperglycemia, insulin resistance, hyperlipidemia, metabolic disturbances, and neurohormonal activation, combined with other risk factors, may promote DCM progression. PA-treated H9c2 cells presented with enhanced levels of ER stress, apoptosis, and lipid deposition, as well as impaired autophagy ( Wu et al, 2020 ). Therefore, to better simulate T2DM, we will maintain the myocytes in “diabetic like” medium of insulin-high glucose ( Davidoff and Ren, 1997 ) or PA-high glucose ( Hu et al, 2019 ) to study the pathological mechanisms in further studies.…”
Section: Discussionmentioning
confidence: 99%